Flexural strength properties of porous concrete pavement incorporating nano black rice husk ash - Putra Jaya, Ramadhansyah; Mohamad Idris, Ali; M. Y., Mohd Ibrahim; Mohd Rosli, Hainin; Haryati, Yaacob; N. A., Hassan; W. I., Mohd Haziman; S., Ekarizan (IOP Publishing, 2019)
Rice husk ash (RHA) as replacement material in the conventional concrete mixture has widely investigated around the world. However, there is a lack of study on nanoparticle produced from black rice husk ash (BRHA) used as a replacement material in porous concrete pavement mixture. Therefore, this study aims to evaluate the flexural strength properties of porous concrete pavement containing nano black rice husk ash. A nano BRHA dosage of 0, 10, 20, 30 and 40% by weight of binder used throughout the experiments. The total cementitious content used was 450 kg/m3 with a water/binder ratio of 0.34. It found that there appears to be an optimum replacement of approximately 10% nano BRHA, during which time the flexural strength and flexural activity index increase significantly.